2017
DOI: 10.1039/c7cp05005d
|View full text |Cite
|
Sign up to set email alerts
|

Scaling relations for the interactions between curved graphene sheets in water

Abstract: The effect of curvature and relative orientation between two curved graphene sheets in aqueous media is quantified by calculating the potential of mean force using molecular dynamics simulations and thermodynamic perturbation. The potential of mean force between two curved graphene sheets is found to scale as U ∼ Rd, where R is the sheet radius of curvature and d is the inter-sheet distance. Further, a simple analytical calculation based on classical Hamaker theory and the Derjaguin approximation also arrives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…While only the separation distance between the two graphene sheets was varied, all other degrees of freedom of the graphene sheets (including translations and rotations) were frozen for the thermodynamic perturbation calculations. More details of our implementation of thermodynamic perturbation for the evaluation of PMF between graphene sheets can be found in our previous publications. ,, The calculated free energy profiles of these systems are shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While only the separation distance between the two graphene sheets was varied, all other degrees of freedom of the graphene sheets (including translations and rotations) were frozen for the thermodynamic perturbation calculations. More details of our implementation of thermodynamic perturbation for the evaluation of PMF between graphene sheets can be found in our previous publications. ,, The calculated free energy profiles of these systems are shown in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…The CHARMM force field was used to model all interatomic interactions, and the TIP3P model was used to describe water molecules. The detailed description of the simulation setup and the method adopted are provided in the Supporting Information of Section S1, and the same information discussed extensively can be found in publications from our group. …”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Never‐theless, Wang et al showed an exceptionally fast charging time of 110 s for this material, obtaining a discharge capacity of 60 mAh g −1 at a rate of 2 A g −1 (Figure b). To obtain an improved capacity by allowing deep insertion of Al 3+ , modified forms of graphene may aid as they have in the past for other materials …”
Section: Aqueous Rechargeable Electrodes For Al‐ion Storagementioning
confidence: 99%